Water and land use systems and natural resources management in the multifunctional landscapes of Western Kenya - Oduor, N.; Zemadim, Birhanu; Adamtey, Noah; Gebrezgabher, Solomie A. (International Water Management Institute, 2025)
Climate change is profoundly affecting water and land-use systems by reducing the availability and accessibility of water resources and accelerating land degradation, leading to the loss of essential nutrients for crop production and biodiversity conservation. Sub-Saharan Africa (SSA) is particularly vulnerable due to inadequate water and land management, a challenge compounded by rapid population growth and increasing demands for improved livelihoods. In multifunctional landscapes, identifying, mapping, and understanding how communities use and manage natural resources is critical for sustainable development. This study was conducted in Kisumu and Vihiga counties in western Kenya to document existing knowledge, technologies, and practices related to soil and water management, cropping systems, resilient farming practices, and natural resource management. The specific objectives were to assess water and land resources, evaluate crop water productivity, examine soil water capture and retention practices, assess agricultural biomass, and understand community perceptions of natural resource use. The study combined a desk review with cross-sectional qualitative and quantitative surveys using multistage, proportionate-to-size sampling. Results showed diverse water sources and land management practices, though irrigation was limited (8%) due to water scarcity, flooding, and lack of lifting technologies. While communities recognized the importance of conservation, resource degradation persisted, underscoring the need for ongoing awareness and promotion of affordable, sustainable water and land-use practices.